Multifaceted interventions for improving spontaneous reporting of adverse drug reactions in a general hospital in China - Huan Fang; Xiaowen Lin; Jun Zhang; Zhen Hong; Kenji Sugiyama; Takao Nozaki; Tetsuro Sameshima; Susumu Kobayashi; Hiroki Namba; Tetsuya Asakawa (BMC, 2017)
Abstract Background The present study investigates changes in spontaneous reporting (SR) compliance and ADR patterns following adoption of a new hospital SR system, and multiple interventions designed for its improvement use under modified drug administration guidelines. Methods In total, 1389 ADR cases were reviewed. Cases were divided into two groups, cases from period 1 (n = 557, from January 2006 to June 2011) under the old SR system and cases in period 2 (n = 832, from July 2011 to December 2016) under the new SR system with multiple interventions to improve physician SR compliance. General information, drug information, and clinical manifestations were investigated and compared between periods. Results Interventions for improved clinician training, education on knowledge, attitudes, and practices (KAP), and economic incentives substantially improved SR adherence. We also found that changing drug usage patterns (based on the new drug administration guidelines) greatly influenced ADR occurrence and type. Conclusions We found the SR compliance can be improved by multifaceted interventions. Drug usage patterns also influence ADR occurrence, so programs tailored for rational use are essential. These results could lead to further improvements in the SR system for ADRs in China, and provide guidance for establishing better methods of pharmacovigilance.